COVID-19 Pandemic Response: Development of Outpatient Palliative Care Toolkit Based on Narrative Communication. (November 2020) - Roberts, Benjamin; Wright, Scott M.; Christmas, Colleen; Robertson, Mariah; Wu, David Shih
Context: The coronavirus disease 2019 (COVID-19) pandemic laid bare the immediate need for primary palliative care education for many clinicians. Primary care clinicians in our health system reported an urgent need for support in advance care planning and end-of-life symptom management for their vulnerable patients. This article describes the design and dissemination of palliative care education for primary care clinicians using an established curriculum development method. Objectives: To develop a succinct and practical palliative care toolkit for use by primary care clinicians during the COVID-19 pandemic, focused on 2 key elements: (i) advance care planning communication skills based on the narrative 3-Act Model and (ii) comfort care symptom management at the end of life. Results: The toolkit was finalized through an iterative process involving a team of end-users and experts in palliative care and primary care, including social work, pharmacy, nursing, and medicine. The modules were formatted into an easily navigable, smartphone-friendly document to be used at point of care. The toolkit was disseminated to our institution's primary care network with practices spanning our state. Early feedback has been positive. Conclusion: While we had been focused primarily on the inpatient setting, our palliative care team at Johns Hopkins Bayview Medical Center pivoted existing infrastructure and curriculum development expertise to meet the expressed needs of our primary care colleagues during the COVID-19 pandemic. Through collaboration with an interprofessional team including end-users, we designed and disseminated a concise palliative care toolkit within 6 weeks.